ANALISIS UNSUR Ag PADA SAMPEL CAIR DENGAN LASER INDUCED BREAKDOWN SPECTROSCOPY (LIBS) - Natalia Declarossy, Sinaga; Suyanto, Hery; Manurung, Manuntun (BULETIN FISIKA; Vol 15 No 1 (2014): BULETIN FISIKA, 2014)
It has been done research on the analysis of Ag element in the liquid electrolyte with Laser Induced Breakdown Spectroscopy (LIBS) through electrolysis method. Observations conducted by LIBS using Nd-YAG laser (1064nm, 7ns). Prior to analyze, first looking for the optimum conditions of experiments had been done. The results showed that the optimum laser energy to the characterization of the elements Ag was 100 mJ and optimum conditions of electric current and time deposition on electrolysis process were 4.93 mA and 10 minutes, respectively. These conditions, next, for the application of quantitative analysis of Ag solution that started from concentration 300 ppm to the lowest concentration and limit of detection obtained 1 ppm.